2019
DOI: 10.1177/1352458519865118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assisted reproductive technology on multiple sclerosis relapses: Case series and meta-analysis

Abstract: Background: Five case series reported increased relapse risk after assisted reproductive technologies (ART) in women with multiple sclerosis (MS), but small numbers and heterogeneous study design limit broader conclusions. Objective: To evaluate the risk of relapses after ART in an independent case series and in aggregated analyses of existing studies. Methods: We compared annualized relapse rate (ARR) in the 3 months after, and 12 months before, ART in (1) an unpublished cohort (Boston: prospectively collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
3
33
0
1
Order By: Relevance
“…5155 Whereas the Boston case series did not have higher ARR after ART compared with before, the overall meta-analysis including this cohort confirmed increased ARR after ART, with a mean ARR increase of 0.92 [95% confidence interval (CI) 0.33–1.51]. 50 On the other hand, Guzman-Soto et al reported that leuprolide acetate, a synthetic analogue of GnRH used in IVF, has a neurotrophic effect on neurofilament, myelin basic protein expression, and axonal morphometry in EAE, thus opening horizons for studying protocols of ART in MS. 56…”
Section: Fertility and Contraceptionmentioning
confidence: 72%
See 1 more Smart Citation
“…5155 Whereas the Boston case series did not have higher ARR after ART compared with before, the overall meta-analysis including this cohort confirmed increased ARR after ART, with a mean ARR increase of 0.92 [95% confidence interval (CI) 0.33–1.51]. 50 On the other hand, Guzman-Soto et al reported that leuprolide acetate, a synthetic analogue of GnRH used in IVF, has a neurotrophic effect on neurofilament, myelin basic protein expression, and axonal morphometry in EAE, thus opening horizons for studying protocols of ART in MS. 56…”
Section: Fertility and Contraceptionmentioning
confidence: 72%
“…52 Similarly, another study, wherein women with MS received GnRH agonist or antagonist, followed by FSH, found that the annualized relapse rate (ARR) increased during 3 months following ART, with correlation to GnRH agonist use and IVF failure. 53 A recent meta-analysis by Bove et al 50 combined five published studies and reported a case series (n = 12). [51][52][53][54][55] Whereas the Boston case series did not have higher ARR after ART compared with before, the overall meta-analysis including this cohort confirmed increased ARR after ART, with a mean ARR increase of 0.92 [95% confidence interval (CI) 0.33-1.51].…”
Section: Fertility and Assisted Reproductive Technologymentioning
confidence: 99%
“…28,29 It is important to consider that counseling should be given about the possibility of an increased risk for MS relapse after ART. 29,30 As with most research, CANPREG-MS has benefits and limitations. As previously stated, this is a real world scenario with no restrictions on a woman's age, disability, MS duration, therapy, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies and clinical reports have provided evidence that ART increases the risk of relapse, number of new or enlarging T2 lesions and gadolinium-enhancing lesions -particularly in the first three months if the ART has been unsuccessful [26,27]. Gonadotropin-releasing hormone (GnRH) agonists stimulate immune cell proliferation; cytokine, chemokine and endothelial growth factor production; and estrogen levels.…”
Section: Assisted Reproductive Technique (Art)mentioning
confidence: 99%